Study of Television Advertising and its Impact on Consumer Behavior in a Sample of Children Aged 9-12 Years (Journal of the College of Education for Women, 2019)
The aim of this study was to study TV advertising and consumer behavior in children and to meet the needs of children. The study included 100 children from Baghdad who were randomly selected from different regions ranging in age from 9-12 years of both males and females. The current research was based on the interview and the completion of special forms prepared for this purpose. This age group was selected for the rare studies conducted on television advertising and limited to different sectors. Data on age and sex were documented, as the results of this study proved The afternoon period was the preferred period for watching the TV show in males, where it was 22%, while the morning period was the female favorite, and it was 23%. The individual viewing pattern was overwhelming in the studied sample, especially in the 11-12 age group. For the male sex and 31% for the female sex while the collective viewing pattern is dominant in the age group (9-10) years, and the musical and animation ads received a high viewing rate and were more favorable for the majority of the sample and for all age groups and both sexes It was noted that the ads of chocolate are the most popular ads of children and then the announcement of fast food and found that the males are more demand for food displayed in the television advertising of the female Wan TV advertising the role and impact in food inta